Use of the SSiB4/TRIFFID model coupled with TOPMODEL to investigate the effects of vegetation and climate on evapotranspiration and runoff in a subalpine basin of southwestern China - Deng, Huiping; Dan, Li; Deng, Huanguang; Xiao, Yan; Wang, Qian (Journal of Environmental Engineering and Landscape Management, 2022)
It is important to understand the response of vegetation dynamics and surface water budget to the changing climate. To investigate the effects of vegetation and climate change on evapotranspiration and runoff on a basin scale, the SSiB4T/TRIFFID (SSiB4/TRIFFID coupled with TOPMODEL) is used to perform long-term dynamic simulations of vegetation succession and the water balance under different climate scenarios for a subalpine basin. The results of all experiments show that fraction of vegetation changes from a dominance of C3 grasses to tundra shrubs and then gradually approaches equilibrium with a dominance of forests. Change to evapotranspiration is very sensitive to temperature changes but is not sensitive to precipitation changes when the temperature remains unchanged. Runoff is very sensitive to changes in both temperature and precipitation. In the increase of temperature, evapotranspiration of forests increases the most among the three vegetation types. From the control run to the [T+5, (1+40%)P] run (A temperature increase of 5 °C, an increase in precipitation of 40%), the role of forests in increasing runoff changes to a reduction in runoff.